Language and dialect contact in Ireland : the phonological origins of Mid-Ulster English - Maguire, Warren (Edinburgh University Press, 2020)
Warren Maguire examines Mid-Ulster English as a key case of new dialect formation, considering the roles of language shift and dialect contact in its phonological development.